2020
DOI: 10.1101/2020.09.02.278119
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Oscillatory entrainment of the Frequency Following Response in auditory cortical and subcortical structures

Abstract: There is much debate about the existence and function of neural oscillatory entrainment mechanisms in the auditory system. The frequency-following response (FFR) is an index of neural periodicity encoding that can provide a vehicle to study entrainment in frequency ranges relevant to speech and music processing. Criteria for entrainment include the presence of post-stimulus oscillations and phase alignment between stimulus and endogenous activity. To test the hypothesis of entrainment, in experiment 1 we colle… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…Research spanning three decades has richly characterized the properties of subcortical FFRs (Chandrasekaran and Kraus, 2010a;Skoe and Kraus, 2010a;Krizman and Kraus, 2019;Coffey et al, 2021), but open questions remain with respect to characteristics of the cortical FFR sources and their contribution to the scalp recorded FFRs. Our study establishes a cross-species (human, macaque, GP) and cross-level (intra-cranial, scalp) platform to study cortical FFRs and their contribution to the scalp-recorded FFRs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research spanning three decades has richly characterized the properties of subcortical FFRs (Chandrasekaran and Kraus, 2010a;Skoe and Kraus, 2010a;Krizman and Kraus, 2019;Coffey et al, 2021), but open questions remain with respect to characteristics of the cortical FFR sources and their contribution to the scalp recorded FFRs. Our study establishes a cross-species (human, macaque, GP) and cross-level (intra-cranial, scalp) platform to study cortical FFRs and their contribution to the scalp-recorded FFRs.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, periodicity code of pitch is thought to be transformed into a rate or rate-place code in the upper brainstem (Plack et al, 2014). Recent studies using magnetoencephalography (MEG) and EEG have challenged these accounts and shown substantial cortical contributions to the scalp FFRs, with a distinct rightward cortical asymmetry (Coffey et al, 2016(Coffey et al, , 2021Hartmann and Weisz, 2019;Gorina-Careta et al, 2021). However, non-invasive MEG and EEG studies require inferences based on distributed source modelling approaches which are relatively less sensitive to deep brain sources.…”
Section: Introductionmentioning
confidence: 99%
“…For more than three decades, the inferior colliculus and the cochlear nucleus were considered the primary neural sources of the FFRs (5,10,11,(35)(36)(37). Emerging research demonstrates a robust cortical contribution to the scalprecorded FFRs (12,(38)(39)(40)(41). The neural dynamics and other response properties of the putative cortical ensembles contributing to the FFRs are poorly understood and will be the main focus of the current study.…”
Section: Introductionmentioning
confidence: 99%
“…The copyright holder for this preprint (which this version posted May 18, 2021. ; https://doi.org/10.1101/2021.05.17.444462 doi: bioRxiv preprint using magnetoencephalography (MEG) have challenged these accounts and shown strong cortical contributions to the scalp FFRs, with a distinct rightward cortical asymmetry (38)(39)(40). However, MEG studies require inferences based on distributional source modelling approaches which are relatively less sensitive to deep brain sources.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation